TLR2-induced CD8+ T-cell deactivation shapes dendritic cell differentiation in the bone marrow during sepsis - Antoni, Anne-Charlotte; Pylaeva, Ekaterina; Budeus, Bettina; Jablonska, Jadwiga; Klein-Hitpaß, Ludger; Dudda, Marcel; Flohé, Stefanie B. (Frontiers in Immunology, 2022)
Sepsis is associated with profound immune dysregulation that increases the risk for life-threatening secondary infections: Dendritic cells (DCs) undergo functional reprogramming due to yet unknown changes during differentiation in the bone marrow (BM). In parallel, lymphopenia and exhaustion of T lymphocytes interfere with antigen-specific adaptive immunity. We hypothesized that there exists a link between T cells and the modulation of DC differentiation in the BM during murine polymicrobial sepsis. Sepsis was induced by cecal ligation and puncture (CLP), a model for human bacterial sepsis. At different time points after CLP, bone marrow and spleen were analyzed in terms of T cell subpopulations, activation, and IFN-g synthesis as well as the number of pre-DCs. Bone marrow-derived DCs were generated in vitro. We observed that naïve and virtual memory CD8+ T cells, but not CD4+ T cells, were activated in an antigen-independent manner and accumulated in the BM early after CLP whereas lymphopenia was evident in the spleen. The number of pre-DCs strongly declined during acute sepsis in the BM and almost recovered by day 4 after CLP which required the presence of CD8+ T cells. Adoptive transfer experiments and in vitro studies with purified T cells revealed that TLR2 signaling in CD8+ T cells suppressed their capacity to secrete IFN-g and was sufficient to change the transcriptome of the bone marrow during sepsis. Moreover, the diminished IFN-g production of CD8+ T cells favored the differentiation of DCs with increased production of the immune-activating cytokine IL-12. These data identify a novel role of CD8+ T cells in the BM during sepsis as they sense TLR2 ligands and control the number and function of de novo differentiating DCs.